Battling Algorithmic Bias. - Kirkpatrick, Keith (Communications of the ACM, 2016)
In this article, the author examines computer algorithms and their possible biases. Particular focus is given to the human decision-making behind these algorithms. Additional topics discussed include the use of algorithms in the criminal justice system, investigative journalism on the topic from the nonprofit organization "Pro Publica," and machine learning engineering.